Comprehensive genome and epigenome characterization of CHO cells in response to evolutionary pressures and over time. Issue 10 (29th April 2016) - Feichtinger, Julia; Hernández, Inmaculada; Fischer, Christoph; Hanscho, Michael; Auer, Norbert; Hackl, Matthias; Jadhav, Vaibhav; Baumann, Martina; Krempl, Peter M.; Schmidl, Christian; Farlik, Matthias; Schuster, Michael; et al.
ABSTRACT: The most striking characteristic of CHO cells is their adaptability, which enables efficient production of proteins as well as growth under a variety of culture conditions, but also results in genomic and phenotypic instability. To investigate the relative contribution of genomic and epigenetic modifications towards phenotype evolution, comprehensive genome and epigenome data are presented for six related CHO cell lines, both in response to perturbations (different culture conditions and media as well as selection of a specific phenotype with increased transient productivity) and in steady state (prolonged time in culture under constant conditions). Clear transitions were observed in DNA‐methylation patterns upon each perturbation, while few changes occurred over time under constant conditions. Only minor DNA‐methylation changes were observed between exponential and stationary growth phase; however, throughout a batch culture the histone modification pattern underwent continuous adaptation. Variation in genome sequence between the six cell lines on the level of SNPs, InDels, and structural variants is high, both upon perturbation and under constant conditions over time. The here presented comprehensive resource may open the door to improved control and manipulation of gene expression during industrial bioprocesses based on epigenetic mechanisms. Biotechnol. Bioeng. 2016;113: 2241–2253. © 2016 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc. Abstract : Six closely related CHO cell lines were studied for their genome and epigenome modifications in response to evolutionary pressures and over time. Full genome and DNA methylation data including analyses for SNPs, InDels, translocations and other structural variants, full genome DNA methylation patterns, and detailed data on histone modifications during a batch culture are presented in a web database atcho-epigenome.boku.ac.at/ .